Assessement of neonatal sepsis and associated factors among neonates admited neonatal intensive care unit in selected public hospitals in Somali Region, Ethiopia - Nur, Abdikani; Osman, Mohamed (The European Research Journal, 2021)
Objectives: To assess neonatal sepsis and associated factors among neonates admitted neonatal intensive care unit in selected public hospitals in Somali region, Ethiopia.Methods: Institution based cross sectional study design was conducted in selected public hospitals. Data was collected using structured questionnaire adopted from other literature, entered into Epi-data version 3.1 and then was exported to SPSS version 23 for analysis. Frequency was used for descriptive analysis. Bivariate analysis was used to determine the association between different risk factors and the outcome variable. Those variables which have significant association at 5% significance level and fulfilling the minimum requirement of 0.2 level of significance with neonatal sepsis was entered for further analysis to multivariate analysis, significance was taken at α = < 0.05.Results: The overall prevalence of this study was 42.9% CI = (38.4-47.8) and associated factors was age of the neonate AOR = 0.085 (CI = 0.01, 0.73), Residence shown AOR = 2.567 (CI = 1.01, 6.5) Gestational age AOR = 1.869 (CI = 1.05, 3.31), Meconium stained Amniotic fluid AOR = 2.718 (CI = 1.89, 6.74), Antenatal care AOR = 8.933 (CI = 4.9, 15.9), and Mechanical ventilation after birth OR = 3.376 (CI = 1.65, 6.88).Conclusions: The present study found that the overall prevalence of neonatal sepsis in selected hospitals was 42.9%. The study identified, Age of the neonate, Residence, Gestational age, Meconium stained amniotic fluid. Antenatal care, Mechanical ventilation after birth. The findings underscore the importance of routine assessment and close monitoring of neonates. It is therefore recommended to have more skilled health personnel and advanced equipment while providing maternal and new-born health care services.